Product Development Based Sensory Evaluation and Physicochemical Characterization of Cashew Apple Bagasse Jam and Technology Transfer to Community - Nurerk, Piyaluk; Junden, Sirisopa (Trends in Sciences, 2021)
Jam type product was successfully developed using cashew apple bagasse from cashew apple juice manufacturing. Proximate analysis of cashew apple bagasse was carried out including soluble and insoluble fiber content. Cashew apple juice was added to 3 different ratios to produce jam type products and their sensory quality was evaluated; 5 percentage cashew apple juice content in Jam product was favored in all sensory parameters. Physicochemical properties of the jam product were analyzed including proximate composition, dietary fiber content, color, viscosity, pH and water activity. The optimum condition to produce cashew apple bagasse prototype was transferred to staffs of local company of Cashewy Phuket Cooperation Limited, Thailand through hands-on training for description and demonstration jam production. The assessment of before and after training was statistically significant at the 0.05 level of significance. The overall evaluation score of technology transfer has obtained the level of most satisfied with the mean score of 4.59. HIGHLIGHTS Residue cashew crude was developed as cashew crude jam The addition of cashew juice was evaluated satisfaction based on sensory test The developed cashew crude jam was investigated physicochemical properties This product was applied to community for technology transfer GRAPHICAL ABSTRACT